Analisis Kompetensi Profesional Guru dalam Mengelola Proses Pembelajaran di SDN Gandong 1 Tahun 2022/2023 - Setiawan, Dicky; Permata, Santy Dinar; Mashuri, Anwas (Civiliza Publishing, Indonesia., 2023)
This research aims to analyze teachers' professional competence in managing the learning process at SDN Gandong 1 in the 2022/2023 academic year. The type of research applied is descriptive qualitative research. Data was obtained through observation, interviews and documentation involving the principal, class teachers and students. Data analysis was carried out by referring to the framework introduced by Miles, Huberman, and Saldana, which includes the stages of data collection, data reduction, data presentation, and drawing conclusions. Findings from the research show that teachers at SDN Gandong 1 have succeeded in applying their professional competence in managing the learning process. They understand the material, structure and scientific concepts that support the learning process, as well as the core competencies and basic competencies of the subjects they teach well. In addition, they have the ability to produce learning materials in innovative ways, continue to improve their level of professionalism on an ongoing basis, and utilize technology, information and communication for self-development in the context of the learning process. Moreover, aspects of the learning process, such as communication during the teaching and learning process, management of learning implementation, responses from students, student participation in learning activities, and evaluation of student learning outcomes, have all been carried out effectively. All of this confirms the success of teachers in developing their competency skills in teaching brilliantly.